2012
DOI: 10.1128/jvi.00453-12
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 Functions as a Porter To Lead Influenza Virus Ribonucleoprotein Complexes to Microtubules

Abstract: -1), a cellular protein that is involved in regulation of cellular transcription and translation. YB-1 translocated to the nucleus from the cytoplasm and accumulated in PML nuclear bodies in response to influenza virus infection. vRNP assembled into the exporting complexes with YB-1 at PML nuclear bodies. After nuclear export, using YB-1 knockdown cells and in vitro reconstituted systems, YB-1 was shown to be required for the interaction of vRNP exported from the nucleus with microtubules around the microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 81 publications
2
51
0
Order By: Relevance
“…The reported viral functions of these cellular cofactors are compiled in Table S4 in the supplemental material. For instance, a role for YB-1 has been described upon infection with influenza virus and dengue virus, a member of the Flaviviridae family, like HCV (71,72). Additionally, human immunodeficiency virus type 1 co-opts DDX3, DDX6, and hnRNP A1 during the late stages of its life cycle (73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…The reported viral functions of these cellular cofactors are compiled in Table S4 in the supplemental material. For instance, a role for YB-1 has been described upon infection with influenza virus and dengue virus, a member of the Flaviviridae family, like HCV (71,72). Additionally, human immunodeficiency virus type 1 co-opts DDX3, DDX6, and hnRNP A1 during the late stages of its life cycle (73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, YB1 plays an important role in the replication of a number of viruses via binding to viral proteins, for example, HIV TAT (Ansari et al, 1999), HIV Rev (Kramer-Hämmerle et al, 2005), large T antigen of polyomavirus (Safak et al, 2002), Hepatitis C virus (HCV) protein NS3/4A (Chatel-Chaix et al, 2011), and influenza viral ribonucleoprotein (RNP) (Kawaguchi et al, 2012). Using an shRNA gene knockdown approach similar to ours, Chatel-Chaix et al (2011 reported that downregulation of YB1 resulted in the reduction of HCV infectious titer by up to 80%; however, down-regulation of YB1 did not influence the expression of viral proteins and the production and stability of vRNA, indicating that knockdown YB1 disrupted the formation of a YB1-NS3/ 4A-vRNA interactome required for recruiting core proteins for virus assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Y-box-binding protein 1 (YB-1) was recently shown to associate with the vRNP export complex. vRNPs are bound in the nucleus by YB-1, where it accompanies the viral gene segments during their transport through the NPC (Kawaguchi et al, 2012). YB-1 appears not to be involved in vRNP export directly but instead exerts its function in the cytoplasm where it plays an important role in the transport of vRNPs to the apical cell surface (Kawaguchi et al, 2012).…”
Section: Transport Of Viral Components To the Assembly Sites Vrnp Tramentioning
confidence: 99%
“…vRNPs are bound in the nucleus by YB-1, where it accompanies the viral gene segments during their transport through the NPC (Kawaguchi et al, 2012). YB-1 appears not to be involved in vRNP export directly but instead exerts its function in the cytoplasm where it plays an important role in the transport of vRNPs to the apical cell surface (Kawaguchi et al, 2012). Another example is the mitogen-activated protein kinase (MAPK)-dependent signalling pathway, which stimulates NEP-dependent vRNP export (Pleschka et al, 2001).…”
Section: Transport Of Viral Components To the Assembly Sites Vrnp Tramentioning
confidence: 99%